American Empire: An Overview of Orientalism of Muslims and Islamophobia - Suzana Muhammad, Sadiya Abubakar Isa, Md Salleh Yaapar, (Opción, 2019)
The research highlights how media, cinema, political discourse or literature portrays Muslims and Islam in a negative light by dwelling on the crimes of only a few Muslims, which in turn creates a stereotype for the Muslims via comparative qualitative research methods. As a result, Orientalism and Islamophobia are rooted in the development of the American empire. In conclusion, the principal subject of discrimination in America today is the Muslims; therefore, it concludes that Islamophobia is the newest and ongoing form of racism in America.